Duch Święty w nauczaniu św. Ildefonsa z Toledo - Wygralak, Paweł (Vox Patrum, 2020)
The article presents the teaching of St. Ildefonsus of Toledo on the Holy Spirit, especially that contained in his writings devoted to the sacrament of baptism. On the basis of selected passages from the Holy Scripture and reflections of earlier authors, the bishop of Toledo emphasizes the truth of the divinity of the Holy Spirit and His equality with the Father and the Son. He also discusses the role of the Holy Spirit in the work of salvation, drawing particular attention to the act of the Incarnation of the Son of God. However, he definitely devotes the most space to the role of the Holy Spirit in the life of every Christian. The Holy Spirit is the one who bestows the necessary grace, enables man to love God and his neighbour, supports him so that he can increase his knowledge of the mysteries of faith. The Holy Spirit gives strength and wisdom in the work of evangelization. In his teachings, Ildefonsus uses the legacy of the earlier Church Fathers, above all Augustine and Isidore of Seville. But he remains original in the form of presenting the difficult truths of the faith. His language is accessible, vivid and at the same time precise.